Identification of cytoplasmic proteins interacting with unliganded estrogen receptor α and β in human breast cancer cells. Issue 11 (18th March 2015) - Stellato, Claudia; Nassa, Giovanni; Tarallo, Roberta; Giurato, Giorgio; Ravo, Maria; Rizzo, Francesca; Marchese, Giovanna; Alexandrova, Elena; Cordella, Angela; Baumann, Marc; Nyman, Tuula A.; Weisz, Alessandro; et al.
<x xml:space="preserve">Abstract</x> Estrogen receptor subtypes (ERα and ERβ) are transcription factors sharing a similar structure but exerting opposite roles in breast cancer cells. Besides the well‐characterized genomic actions of nuclear ERs upon ligand binding, specific actions of ligand‐free ERs in the cytoplasm also affect cellular functions. The identification of cytoplasmic interaction partners of unliganded ERα and ERβ may help characterize the molecular basis of the extra‐nuclear mechanism of action of these receptors, revealing novel mechanisms to explain their role in breast cancer response or resistance to endocrine therapy. To this aim, cytoplasmic extracts from human breast cancer MCF‐7 cells stably expressing tandem affinity purification‐tagged ERα and ERβ and maintained in estrogen‐free medium were subject to affinity‐purification and MS analysis, leading to the identification of 84 and 142 proteins associated with unliganded ERα and ERβ, respectively. Functional analyses of ER subtype‐specific interactomes revealed significant differences in the molecular pathways targeted by each receptor in the cytoplasm. This work, reporting the first identification of the unliganded ERα and ERβ cytoplasmic interactomes in breast cancer cells, provides novel experimental evidence on the nongenomic effects of ERs in the absence of hormonal stimulus. All MS data have been deposited in the ProteomeXchange with identifier PXD001202 (http://proteomecentral.proteomexchange.org/dataset/PXD001202).